Langues pour étudiants spécialistes d'autres disciplines : de l'amphithéâtre à l'autonomie d'apprentissage - Cédric Brudermann; Nicole Poteaux (Centre National d'Enseignement à Distance, 2015)
While current European policies are promoting new skills, enabling students to both work and interact in international contexts, the field of "language for specific purposes" at university level in France tends to use the traditional amphitheater/classroom settings - which are specific to non linguistic academic disciplines - as their main teaching and learning paradigm. However, current knowledge concerning learning processes shows that interaction is of utmost importance to allow one to build new knowledge, and - in the case of foreign languages - foster proficiency development. In this respect, information and communication technologies have the potential to facilitate the design of new learning environments. But, by cascading effect, their implementation requires an upstream thought process, i.e. an instructional design phase, itself supported by epistemological foundations.This paper aims at highlighting how research can shape and nourish a rigorous instructional design approach and further lead to the implementation of well thought-out teaching and learning systems dedicated to foreign languages. To illustrate this, two experimental devices set up in two French universities (University Pierre and Marie Curie and University of Strasbourg) will be presented. A discussion on large-scale deployment of distance education solutions and on tailor-made languages for specific purposes teaching and learning practices in the current sociopolitical context will follow.